Analisis Perlindungan Hak Cipta Penggunaan Nama & Visual Artis Korea (SM Entertainment) Pada Novel & Serial “Dikta dan Hukum” - Khaira Alfiyya Irwandi (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Korean fever or often referred to as the Hallyu Wave is now continuing to grow along with technological developments and ease of internet access. Dikta and Law, by Dhia'an Farah, is one of the many popular fiction stories that is fortunate to be currently being broadcast as a series on WeTV. However, behind the success of the Dikta and Hukum story, there was controversy that arose. The name Jeno, one of the characters in the story Dikta and Hukum, has become a debate on social media, especially for NCT Dream fans. The reason is, Jeno is the stage name of one of the members of NCT Dream (Lee Jeno) and is considered to be used illegally in the Dikta and Hukum series. This controversy arose because the novel writer and series production party used the name Jeno without the permission of the name owner or his agency, namely SM Entertainment. This research aims to analyze copyright protection for the use of names and visuals of Korean artists (SM Entertainment) in the novel and series "Dikta and Hukum". This research uses qualitative methods with an exploratory study approach. Copyright regulations for the use of artists' names and visuals in literary works, novels and TV series are contained in Article 43 of Law no. 28 of 2014 concerning Copyright point d only states that the distribution of copyrighted content is not commercialized, it does not constitute a Copyright violation. Apart from that, this issue is also regulated in the Constitution of the Republic of Korea in Copyright Act Article 137. Dikta and Hukum works in both novels and TV series are both considered to violate copyright because of the use of the artist's name on the character and the artist's photo as promotional content. Even though the Dikta and Law case did not reach the court table, issues related to copyright violations in the K-pop world must continue to be raised and strict action will be taken against violators because it has become a habit that is considered permissible for many people.